Re-conceptualizing the role(s) of science in biodiversity conservation - Evans, Megan C (Environmental conservation, 2021)
Science, as both a body of knowledge and a process of acquiring new knowledge, is widely regarded as playing a central role in biodiversity conservation. Science undoubtedly enhances our understanding of the drivers of biodiversity loss and assists in the formulation of practical and policy responses, but it has not yet proved sufficiently influential to reverse global trends of biodiversity decline. This review seeks to critically examine the science of biodiversity conservation and to identify any hidden assumptions that, once interrogated and explored, may assist in improving conservation science, policy and practice. By drawing on existing reviews of the literature, this review describes the major themes of the literature and examines the historical shifts in the framing of conservation. It highlights the dominance of research philosophies that view conservation through a primarily ecological lens, changes in the goal(s) of conservation and a lack of clarity over the role(s) of science in biodiversity conservation. Finally, this review offers a simple framework to more clearly and consistently conceptualize the role(s) of science in biodiversity conservation in the future. Greater critical reflection on how conservation science might better accommodate multiple knowledges, goals and values could assist in ‘opening up’ new, legitimate pathways for biodiversity conservation.